Layered CAD/CSG geometry for spatially complex radiation transport scenarios. (February 2023) - Biondo, Elliott; Davidson, Gregory; Ade, Brian
Abstract: Many spatially complex fission, fusion, and national security Monte Carlo (MC) radiation transport scenarios involve combining computer-aided design (CAD) models with constructive solid geometry (CSG) models. A layered geometry method has been implemented in the Shift MC code to address this need. With layered geometry, multiple CAD and/or CSG models can be clipped, translated, rotated, and placed in overlapping layers to form transport-ready geometries. The utility of this method is demonstrated with two problems: (1) a fixed-source simulation with a layered geometry consisting of a LiDAR-generated CAD model of the Combined Arms Collective Training Facility urban environment overlaid with CSG models of a mock hotel and a detector apparatus, and (2) a k -eigenvalue calculation using a layered geometry model of the Transformational Challenge Reactor consisting of CAD fuel elements placed in a CSG core. Tallied particle flux distributions match expectations, but tracking robustness must be improved prior to general-purpose use. Highlights: New method for combining CAD and CSG models for Monte Carlo radiation transport. Demonstrated with a LiDAR-generated CAD model of an urban environment. Demonstrated with a reactor consisting of complex fuel elements modeled in CAD.